Fashion spheres – from a systemic to a sphereological perspective of fashion. Issue 4 (3rd October 2016) - Laurell, Christofer
Abstract : Purpose: The purpose of this paper is to explore how the fragmentation of the fashion system can be conceptually explained by drawing on Peter Sloterdijk's theory of spheres. Design/methodology/approach: By conceptually discussing the changing nature of the fashion system and the institutional pressures exerted on fashion systems as a result of digital technology, the fundamental conceptual underpinnings of the theory of spheres are applied to these developments in order to explain the character of the contemporary organization of fashion. Findings: Based on the conceptual analysis, this paper illustrates how a sphereological perspective to fashion provides a conceptual approach to explain the transformation and fragmentation of fashion systems. Originality/value: This paper contributes to the field of fashion marketing and management by demonstrating how the concept of fashion spheres can explain social arrangements going beyond the boundaries of fashion systems and the associated implications that this brings to bear on the role of fashion.